2018 Consensus framework for good assessment. (2nd November 2018) - Norcini, John; Anderson, M. Brownell; Bollela, Valdes; Burch, Vanessa; Costa, Manuel João; Duvivier, Robbert; Hays, Richard; Palacios Mackay, Maria Felisa; Roberts, Trudie; Swanson, David
Abstract: Introduction: In 2010, the Ottawa Conference produced a set of consensus criteria for good assessment. These were well received and since then the working group monitored their use. As part of the 2010 report, it was recommended that consideration be given in the future to preparing similar criteria for systems of assessment. Recent developments in the field suggest that it would be timely to undertake that task and so the working group was reconvened, with changes in membership to reflect broad global representation.Methods: Consideration was given to whether the initially proposed criteria continued to be appropriate for single assessments and the group believed that they were. Consequently, we reiterate the criteria that apply to individual assessments and duplicate relevant portions of the 2010 report.Results and discussion: This paper also presents a new set of criteria that apply to systems of assessment and, recognizing the challenges of implementation, offers several issues for further consideration. Among these issues are the increasing diversity of candidates and programs, the importance of legal defensibility in high stakes assessments, globalization and the interest in portable recognition of medical training, and the interest among employers and patients in how medical education is delivered and how progression decisions are made.